Olive Nutritional Status and Tolerance to Biotic and Abiotic Stresses - Fernández-Escobar, Ricardo (Frontiers in Plant Science, 2019)
The role of nutrients in plant growth is generally explained in terms of their functions in plant metabolism. Nevertheless, there is evidence that plant tolerance or resistance to biotic or abiotic stresses could be affected by the nutritional status. Although not well studied, an adequate nutritional status for optimal plant growth is thought to also be optimal for plant tolerance to stress. Considering the current global trend towards sustainability, studies that clarify the relationships between nutrition and stress are of great interest. For example, potassium plays an important role in the regulation of water status in the olive, improving drought tolerance, while calcium is involved in sodium exclusion mechanism, which can increase tolerance to salinity. Nitrogen excess, in contrast, increases susceptibility to spring frost and olive leaf spot. Silicon is not an essential element for plant growth, but it is considered a beneficial element; among its roles in the control of pests and diseases is the formation of a physical barrier that occurs through silicon deposition in the epidermal cells of the leaves. The presence of soluble silicon also facilitates the deposition of phenolic and other compounds at sites of infection, which is a general defense mechanism to pathogen attack. In the olive, silicon application, either by foliar sprays or through irrigation water, reduces the incidence of olive leaf spot. This review summarizes the current status of olive nutrition, the relationships with biotic and abiotic stresses, and the effects of silicon.